Pengaruh Human Capital, Intangible Asset, Diversifikasi dan Investasi Teknologi Informasi terhadap Financial Distress dalam Situasi Covid-19 - Whidia Bragasti Pangi; Rosiyana Dewi (SAFE-Network, 2023)
This study aims to examine the effect of Human Capital, Intangible Assets, Diversification and Information Technology Investment on Financial Distress in the Covid-19 Situation. The population in this study are Primary and Non-Primary Consumer companies listed on the Indonesia Stock Exchange (IDX) in the 2019-2021 period. The data used is secondary data obtained from annual reports or company financial reports through the website www.idx.co.id or the website of each company. The study used a purposive sampling method with several criteria and the results obtained were 114 sample data. Methods of data analysis using descriptive test, classic assumption test and multiple linear regression test using SPSS software. The results of this study indicate that: Human Capital has no effect on Financial Distress, Intangible Assets have no effect on Financial Distress, Diversification has a negative effect on Financial Distress, Information Technology Investment has no effect on Financial Distress.